The Soviet and British Governments’ Policies Concerning Participation of Women in Paramilitary Organizations of the Interwar Period - Залєток, Наталія (Український історичний журнал, 2022)
The aim of this article is to compare the policies of the British and Soviet governments regarding the participation of women in paramilitary organizations of the interwar period. The research methodology is based on the principles of historicism and consistency. Both general scientific (analysis and synthesis, abstraction, system analysis, generalization) and special-historical (critical analysis of sources, retrospective, historical-comparative) methods, as well as the gender approach were used. The scientific novelty. The article compares for the first time the peculiarities of the participation of Soviet and British women in paramilitary organizations of the interwar period in the context of state policy in this area. Conclusions. The author concludes that the approaches of the authorities to the involvement of British and Soviet women in paramilitary organizations differed significantly and directly depended on the foreign policies of these countries. In the USSR, which despite its pacifist statements during the interwar period gradually prepared for war, its government in the 1920s began to take specific steps for organization of military training of its population without any distinction based on sex. In Great Britain, against the background of economic crisis and peculiarities of foreign policy, women have long been out of such training. In addition, both countries significantly differed in the patterns of behaviour of women imposed by their governments and societies. In particular, in the British public discourse, women were represented as a noncombat, auxiliary force during the future war, the femininity of members of women’s paramilitary organizations was emphasized. Instead, the imposed pattern of women’s behaviour in the Soviet Union was the opposite. They were strongly encouraged to follow the male example; the possibility of their participation in the war as soldiers was often emphasized. At the same time, they shared common arguments in campaigning for women to join paramilitary organizations and held public events to promote such organizations.